The successful marketing plan : a disciplines and comprehensive approach - Hiebing, Roman G.; Cooper, Scott W. (Lincolnwood, Ill : NTC Business Books, 1997)
This book provides with a practical and proven, step-by-step guide for preparing your own marketing plan.
Keywords: Marketing; Management; Marketing -- Planning